Panoramic Radiography Features of Medication-Related Osteonecrosis of the Jaws (MRONJ) - Rossana Izzetti; Stefano Gennai; Pierpaolo De Francesco; Elisabetta Carli; Filippo Graziani; Marco Nisi (Hindawi Limited, 2023)
The diagnosis of medication-related osteonecrosis of the jaws (MRONJ) relies on the application of the clinical criteria stated in the American Association of Oral and Maxillofacial Surgeons position paper. The role of diagnostic imaging in integrating MRONJ clinical assessment is still debated, as pathognomonic imaging features have not been yet recognized. The present study retrospectively evaluated the radiographic signs of MRONJ on panoramic radiography with the aim of describing the characteristics of the lesions at different stages of the disease. The presence of alterations of the lamina dura (thickening or loss), the persistence of the alveolar socket following tooth extraction, and bone alterations (including sequestrum, sclerosis, osteolysis, mandibular canal enhancement, pathologic fracture, sinus involvement, and periosteal reaction) were investigated. The occurrence of each radiographic sign was stratified depending on oral status, antiresorptive pharmacological treatment administered, and general health variables. A weak relationship between radiographic signs and disease stage was observed. Mandibular canal enhancement was associated with the advanced disease stage (p-value < 0.001). The distribution of the different radiographic features was not influenced by the underlying disease (osteoporosis or oncologic disease) treated with antiresorptive drugs. Bone sequestrum was more frequently encountered in the mandible. Panoramic radiography appears to be a valid support in the assessment of MRONJ lesions. The clinician should be aware of the signs associated with MRONJ occurrence in order to improve the diagnostic performance and provide adequate treatment.